Cost Reduction in Steel-Making Through The Application of Scheduling using Decision Support System - Putra, Krisna; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2013)
Basic metal industries, which include steel industry, are very sensitive to raw material costs. As a result, volatility and rate of increase in raw material costs have a significant impact on the sustainability of the steel industry. To offset the margin pressure due to the current problem, the company should focus on improving operational efficiency by running various programs in order to reduce operating costs and improve the quality of the output. As a complement to these steps, this paper will specifically introduce the Decision Support System (DSS) to solve production scheduling issue in steelmaking operations. The purpose of the scheduling are to reduce the waiting time between the processes in the steel making as well as to increase the yield, which in turn can be used to reduce the cost of production. The simple loading heuristics with forward and backward loading will be used to solve scheduling problems.The basic idea of the proposed system is to treat Continuous Casting Machine (CCM) process as a capacity-constrained resource. On this approach, CCM treated as a determinant of the production rate to entire system. Time scheduling in the steelmaking operation have high complexity due to the strict requirements and uncertainties. The design solution using the DSS is intended also to anticipate when the assumptions fail or not fulfilled, so that manual intervention is needed to bridge the gap in making a feasible schedule.DSS would have an important role in daily operation of steel making to reduce cost. This role will become a vital role in the future, in line with the use of hot metal from the Blast Furnace to Electric Arc Furnace (EAF), since arrival of hot metal would occur periodically in a certain time interval.Â Keywords: Steel making, Scheduling, Theory of Constraints, Decision Support System